Breast cancer dormancy: need for clinically relevant models to address current gaps in knowledge - Grace G. Bushnell; Abhijeet P. Deshmukh; Petra den Hollander; Ming Luo; Rama Soundararajan; Dongya Jia; Herbert Levine; Sendurai A. Mani; Max S. Wicha (npj Breast Cancer, 2021)
Abstract Breast cancer is the most commonly diagnosed cancer in the USA. Although advances in treatment over the past several decades have significantly improved the outlook for this disease, most women who are diagnosed with estrogen receptor positive disease remain at risk of metastatic relapse for the remainder of their life. The cellular source of late relapse in these patients is thought to be disseminated tumor cells that reactivate after a long period of dormancy. The biology of these dormant cells and their natural history over a patient’s lifetime is largely unclear. We posit that research on tumor dormancy has been significantly limited by the lack of clinically relevant models. This review will discuss existing dormancy models, gaps in biological understanding, and propose criteria for future models to enhance their clinical relevance.